Automatic Continuous CRT Optimization to Improve Hemodynamic Response: An Italian Single-Center Experience - Gregorio Covino; Mario Volpicelli; Paolo Capogrosso (International Journal of Vascular Medicine)
Background. Optimization of cardiac resynchronization therapy (CRT) settings after implant can improve response to therapy. In this Italian single-center experience, we investigated the rate of hemodynamic and clinical response in heart failure patients treated with continuously and automatically optimized CRT. Methods. Patients were selected from June 2015 to April 2017 according to the most recent CRT guidelines; all were in sinus rhythm at implant and received a CRT-defibrillator system equipped with SonR, which automatically optimizes AV and VV delays every week. SonR was activated just after implant and remained active during follow-up. The rate of hemodynamic response (R-HR) was defined as ΔLVEF>5%, super-response (R-HSR) as ΔLVEF>15%, and clinical response as a negative transition of NYHA class≥−1 at 6 months follow-up vs. baseline (preimplant). Results. Mean follow-up for the 31 patients (aged 69.9±9.4 years; 61% male; NYHA class II/III 19%/81%; ischemic etiology 65%) was 6±0.7 months. At baseline, LVEF was 29.1%±4.7% and QRS duration 146±13 ms. LBBB morphology was observed in 65%. At 6 months, R-HR was 74% (23/31), R-HSR 32% (10/31), and clinical response rate 77% (24/31). Hemodynamically, patients with ischemic etiology benefited more than those without ischemic etiology, both in terms of response (80% versus 64%) and super-response (35% versus 27%). Conclusions. Continuous automatic weekly optimization of CRT over 6 months consistently improved R-HR, R-HSR, and clinical response in NYHA class II/III heart failure patients versus baseline. Patients with ischemic etiology in particular may benefit hemodynamically from this type of CRT optimization.